Analysis of swimming techniques using vortex traces - Ungerechts, B.; Persyn, U.; Colman, V. (coachesinfo.com, 2000)
Propulsion in water is based on the interaction of motion body and water, respectively (under the condition of limited energy reservoir). The swimming movements are transmitting momentum. The transfer is mediated via a counter bearing (a term indicating the application of Newton's 3rd Law). In water the traces of these counter bearings are useful for discussions about the efficiency of swimming techniques. Here the traces of vortex (a common term for mass of whirling fluid) are emphasised. Vortices occur in different organized patterns, as trailing vortex next to the hands (front driven) or rolling vortex in the wake of the feet (rear driven). Trailing vortices create a zone of underpressure: it is hypothised that the hand is prevented by this underpressure from the intended pull through the water and thus the action of the trunk-arm muscles push the body past the hand. Rolling vortex may transfer a power stroke to the body in case the sense of its rotation is altered. Content: - Hydrodynamical Concepts for Swimming Experts . Vortex, drag and energy balance . Examples of self propulsion . Production of counter bearing in human swimming . Thrust Production via Vortex . Flow visualisation . The momentum-impulse couple of vortex REAR DRIVEN bodies . Practical implications related to rear driven bodies . The momentum-impulse couple of vortex FRONT DRIVEN bodies . Practical implications related to front driven bodies